Attempted predation by introduced salmonids on a native catfish in an Andean River in Argentina - Valdez Ovallez, Franco Miguel (2023)
Interspecific predator-prey interactions play an important role in the structure of communities. However, predation events in the wild are rare, and difficult to observe, and rarely documented. The objective of this work is to report the attempted predation on Hatcheria macraei by some of the salmonids with which it occurs in syntropy. During a survey of ichthyofauna in the Castaño River, an adult specimen of H. macraei was captured with evidence of a bite on the caudal fin. Despite not having been able to make the specific identification of the predator in the predation attempt on H. macraei, this report adds to the enormous base of information on the devastating effects of introduceds salmonids on aquatic ecosystems and the native species that live there inhabit. It is necessary to control the expansion of salmonids, by protecting areas of high value for native fish and prohibiting future aquaculture projects to prevent the invasion of this species to new locations in these aquatic ecosystems.